2005
DOI: 10.1038/nsmb886
|View full text |Cite
|
Sign up to set email alerts
|

Specific and potent RNAi in the nucleus of human cells

Abstract: RNA interference (RNAi) has become a research tool to control gene expression in various organisms and holds potential as a new therapeutic strategy. The mechanism of small interfering RNA (siRNA)-mediated RNAi involves target mRNA cleavage and destruction in the cytoplasm. We investigated siRNA-mediated induction of RNAi in the nucleus of human cells. Notably, we observed highly efficient knockdown of small nuclear RNA 7SK by siRNA. siRNA- and microRNA-programmed RNA-induced silencing complexes (RISCs) were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
247
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(269 citation statements)
references
References 47 publications
18
247
1
Order By: Relevance
“…Interestingly, they demonstrated that, at least for miR29b, it is a distinctive hexanucleotide element (AGUGUU) that distinguishes miR-29b from its family member miR-29a and guides its nucleus import. Consistently, studies have also reported the presence of active miRNA effectors, such as Argonaute proteins, in the nucleus (6). These findings suggest that there are mechanisms to guide the cytoplasmic-nuclear transport of miRNAs and Argonaute proteins and that miRNAs, after re-entering into the nucleus, may also have biological functions.…”
supporting
confidence: 64%
“…Interestingly, they demonstrated that, at least for miR29b, it is a distinctive hexanucleotide element (AGUGUU) that distinguishes miR-29b from its family member miR-29a and guides its nucleus import. Consistently, studies have also reported the presence of active miRNA effectors, such as Argonaute proteins, in the nucleus (6). These findings suggest that there are mechanisms to guide the cytoplasmic-nuclear transport of miRNAs and Argonaute proteins and that miRNAs, after re-entering into the nucleus, may also have biological functions.…”
supporting
confidence: 64%
“…Indeed, previous reports stated that nuclear-localized ncRNA such as RN7SK (Robb et al 2005;Berezhna et al 2006), MALAT1 (Tano et al 2010;Miyagawa et al 2012), and NEAT1 (Clemson et al 2009) could be silenced by siRNAs. There are at least two possibilities for silencing nuclear-localized RNA by siRNA: (1) The component of siRNA-induced silencing localized in the nucleus can function to cleave endogenous nuclear target RNAs in the nucleus (Robb et al 2005). (2) The cytoplasmic RISC cleaves endogenous nuclear target RNAs at the M phase of the cell cycle when the nuclear envelope disassembles and nuclear components, including nuclear ncRNAs, are contacted by cytoplasmic components such as the RISC complex.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian studies are consistent with this scenario; sRNA-loaded RISC in the cytoplasm consists of a large AGO-based complex, whereas in the nucleus, RISC consists of little more than AGO and its loaded sRNA. [75][76][77] Figure 4B illustrates a proposed pathway for miRNA-directed expressional regulation of nuclear-localized transcripts. Recent studies have localized the miRNA biogenesis machinery proteins DCL1, DRB1 and SE to the nucleus specialized D-bodies.…”
Section: Discussionmentioning
confidence: 99%